Porous biomass fly ash-based geopolymers with tailored thermal conductivity. (15th April 2016) - Novais, Rui M.; Buruberri, L.H.; Ascensão, G.; Seabra, M.P.; Labrincha, J.A.
Abstract: In this work novel, porous biomass fly ash-based-geopolymers were produced by using hydrogen peroxide as pore forming agent. This innovative material can help to mitigate the energy losses inside buildings, while simultaneously reducing the volume of generated wastes, thus contributing towards sustainable construction. Results demonstrate that the content of hydrogen peroxide controls the geopolymer physical properties such as porosity, mechanical resistance and thermal conductivity. The latter allows the production of geopolymers displaying suitable properties for thermal insulation applications. Geopolymers exhibiting thermal conductivity as low as 0.107 W/m K and a density of 560 kg/m 3 were produced, showing the potential of these materials in applications requiring lightweight and low thermal conductivity materials. Besides this material is produced using a simple and cost effective approach, promoting waste valorization by reuse of biomass fly ash, which further demonstrates its potential. Graphical abstract: Highlights: Lightweight and low thermal conductivity fly ash based-geopolymers were developed. The excellent features allow its application as partition board and wall panels. This novel product restrains energy losses inside buildings. The environmental problems associated with biomass fly ash waste are mitigated.